Blue light photobiomodulation induced osteosarcoma cell death by facilitating ferroptosis and eliciting an incomplete tumor cell stress response - Yang, Jiali; Fu, Qiqi; Jiang, Hui; Zhong, Hongyu; Qin, Hao Kuan; Miao, Xiaojing; Li, Yinghua; Liu, Muqing; Yao, Jinghui (Journal of photochemistry and photobiology. B, Biology, 2024)
To investigate the potential of blue light photobiomodulation (PBM) in inducing ferroptosis, a novel form of regulated cell death, in OS cells, considering its known effectiveness in various cancer models. In this investigation, we exposed human OS cell lines, HOS and MG63, to different wavelengths (420, 460 and 480 nm) of blue light at varying irradiances, and examined cellular responses such as viability, apoptosis, levels of reactive oxygen species (ROS), and mitochondrial membrane potential (MMP). Transcriptome sequencing was employed to unravel the molecular mechanisms underlying blue light-induced effects, with validation via quantitative real-time PCR (qRT-PCR). Our findings revealed a wavelength- and time-dependent decrease in cell viability, accompanied by increased apoptosis and oxidative stress. Transcriptomic analysis identified differential expression of genes associated with ferroptosis, oxidative stress, and iron metabolism, further validated by qRT-PCR. These results implicated ferroptosis as a significant mechanism in the blue light-induced death of OS cells, potentially mediated by ROS generation and disruption of iron homeostasis. Also, An incomplete stress response was observed in MG63 cells induced by blue light exposure. Hence, blue light PBM holds promise as a therapeutic approach in OS clinical investigations; however, additional exploration of its underlying mechanisms remains imperative. •420 and 460 nm blue light inhibited OS cells viability and promoted apoptosis.•Blue light initiated OS cells ferroptosis via PTGS2 upregulation and GPX4 suppression.•Blue light PBM induced G2/M arrest in OS cells, possibly via CDKN1A.•Blue light provoked an incomplete stress response in MG63 cells.•SLC7A11 expression is pivotal in blue light-induced cell death in OS.